Faktor-Faktor Penyebab Terjadinya Pidana Penganiayaan Terhadap Pengemudi Ojek Online di Gorontalo - Farhan Hiola; Lisnawaty W. Badu; Julius T. Mandjo (Universitas Sains dan Teknologi Komputer, 2023)
This study aims to analyze the factors that cause criminal persecution of online motorcycle taxi drivers in Gorontalo. The research method used is empirical juridical research which aims to analyze the problem by combining legal materials (which are secondary data) with primary data obtained in the field. The application of criminal sanctions against acts of persecution against online motorcycle taxi drivers in Gorontalo is not running as it should. The existence of leniency towards law enforcement is certainly a problem that needs to be a common concern, especially in terms of its resolution, if you look at the reality that occurs, the cases that occur in its application should be categorized as premeditated persecution with article 353 of the Criminal Code, and other cases can be categorized as light persecution article 351 of the Criminal Code. However, in reality the application of criminal sanctions against these cases is not in accordance with the provisions in the Law, in this case the Criminal Code. In addition, the factors causing the persecution of online ojek are jealousy, violation of the green zone, scramble for passengers, envy, service, and customer dissatisfaction.